A nanomachined optical logic gate driven by gradient optical force - Tao, J. F. (2013)
In this letter, a nanomachined optical logic gate using optical gradient force is demonstrated. The device consists of a partially free-hanging silicon double-ring resonator developed by the nano-electro-mechanical system technology. The logic NOR gate function is demonstrated at 20 Mb/s with a high extinction ratio of about 21.3 dB. This proposed NOR gate has the advantages of low power consumption (∼0.5 mW), highly compacted size (40 μm × 45 μm), and easy batch fabrication which has potential applications in silicon-photonic integration for digital signal processing.